Penerapan Sistem Gamifikasi pada Learning Management System - Garnisa, Sandra Budi; Tresnawati, Dewi; Rahayu, Sri (Jurnal Algoritma, 2023)
Currently, fun learning is rarely used by educators, educators more often use the concept of learning by delivering material and assignments carried out full time during learning hours which can make students bored. The concept of gamification in learning is a concept that takes game elements which is expected to make students motivated and enthusiastic in understanding the lessons given by educators. The aim of this research is to apply gamification to the Learning Management System (LMS) so that educators can create content such as quizzes, interactive videos and presentations. In the system there are rewards that make students interested in doing assignments because there is a sense of satisfaction like playing games and can help educators to find out their students' understanding. In making this system, the Multimedia Development Life Cycle method was used with 6 stages, namely concept, design, material collection, assembly, testing and distribution. The final result of this research is a gamification concept in the LMS that applies the LevelUp and badge features, namely giving awards and points by displaying the results obtained in the form of increasing the level of each student on the leaderboard and giving badges according to the criteria determined by the admin and lecturer.